The CCAFS Flagship Program 4 Trial on Results-Based Management: Progress Report - Thornton, Philip K.; Schuetz, Tonya; Förch, Wiebke; Campbell, Bruce M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This document summarises what was achieved during 2014 by the CCAFS RBM trial. This is followed by a discussion of the prerequisites for a CRP to implement successful RBM, what we mean by “successful RBM”, what has worked according to expectations, and what was done when things did not work out as expected. We summarise a few key results from an on-line survey of project participants conducted in November. We conclude with a summary of our overall learnings about RBM during 2014.